THE PORTRAIT OF ENGLISH LANGUAGE SUBJECT IN AN INDONESIAN PRIVATE HIGHER EDUCATION OF COMPUTER SCIENCE (HECS) - Deuis Sugaryamah (University of Kuningan, 2013)
Abstract: At the tertiary level in Indonesia, English language subject is mandatory as a general education course, especially for those non English programs/ departments. How this subject be positioned in an Indonesian Private Higher Education of Computer Science (HECS)â€™ curriculum, that later breeds the representation of the subjects on its teaching materials and its teaching and learning process by the teacher, and the studentsâ€™s perceptions on such implementation of English subjects in the classroom become the concerns of this study. Qualitative research by using interviews, questionnaires and documents were used to collect the data. From the study, it was found that in this institution English is considered as an English for Speciï¬c Purposes(ESP), though regarded as a minor subject, yet itsexistence is considered as important. This perception is acceptable by all stakeholder (the institution, the lecturer and the students).Keywords: English, Higher Education of Computer Science, English for Speciï¬c Purposes